2021
DOI: 10.1186/s12864-021-07410-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals the glycolipid metabolism response mechanism in the liver of genetically improved farmed Tilapia (GIFT, Oreochromis niloticus) under hypoxia stress

Abstract: Background Dissolved oxygen (DO) in the water is a vital abiotic factor in aquatic animal farming. A hypoxic environment affects the growth, metabolism, and immune system of fish. Glycolipid metabolism is a vital energy pathway under acute hypoxic stress, and it plays a significant role in the adaptation of fish to stressful environments. In this study, we used multi-omics integrative analyses to explore the mechanisms of hypoxia adaptation in Genetically Improved Farmed Tilapia (GIFT, Oreochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 74 publications
3
18
0
Order By: Relevance
“…Its activation can stimulate lipid biosynthesis [ 88 ] and regulate lipid deposition by activating lipogenesis and inhibiting fatty acid oxidation [ 89 ]. Multi-omics analyses revealed that the insulin signaling pathway was downregulated in the liver of O. niloticus under hypoxia stress [ 90 ]. In our work, the GSEA data were more inclined to indicate a downregulated insulin signaling pathway in the liver of M. salmoides under the HD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Its activation can stimulate lipid biosynthesis [ 88 ] and regulate lipid deposition by activating lipogenesis and inhibiting fatty acid oxidation [ 89 ]. Multi-omics analyses revealed that the insulin signaling pathway was downregulated in the liver of O. niloticus under hypoxia stress [ 90 ]. In our work, the GSEA data were more inclined to indicate a downregulated insulin signaling pathway in the liver of M. salmoides under the HD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathologic conditions can induce tissue hypoxia, which is an important mediator of lipid metabolism [ 30 , 31 ]. Chronic and acute alcohol intake stimulates hepatic oxygen consumption, and subsequently causes hepatic hypoxia, leading to Hif pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previously described method ( 17 ), liver tissues were prepared from the CON and SPH groups for liquid chromatograph–mass spectrometer (LC–MS) analysis. The tissue samples (~50 mg) were homogenized in pre-cooled 50% methanol buffer (120 μl) using a high-throughput TissueLyser (Xinzhi Biotechnology Co., Ltd. Ningbo, China).…”
Section: Methodsmentioning
confidence: 99%